Thermochromism of CuI tetrakisguanidine complexes: reversible activation of metal-to-ligand charge-transfer bands - Wiesner, Sven; Wagner, Arne; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2015)
Abstract Tetranuclear, intensely blue-coloured CuI complexes were synthesised in which two Cu2X3? units (X=Br or I) are bridged by a dicationic GFA (guanidino-functionalised aromatic) ligand. The UV/Vis spectra show a large metal-to-ligand charge-transfer (MLCT) band around 638?nm. The tetranuclear ?low-temperature? complexes are in a temperature-dependent equilibrium with dinuclear CuI ?high-temperature? complexes, which result from the reversible elimination of two CuX groups. A massive thermochromism effect results from the extinction of the strong MLCT band upon CuX elimination with increasing temperature. For all complexes, quantum chemical calculations predict a small and method-dependent energy difference between the possible electronic structures, namely CuI and dicationic GFA ligand (closed-shell singlet) versus CuII and neutral GFA ligand (triplet or broken-symmetry state). The closed-shell singlet state is disfavoured by hybrid-DFT functionals, which mix in exact Hartree?Fock exchange, and is favoured by larger basis sets and consideration of a polar medium.